Human Interface and the Management of Information. Information and Knowledge in Context : 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings, Part II - Yamamoto, Sakae; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The two-volume set LNCS 9172 and 9173 constitutes the refereed proceedings of the Human Interface and the Management of Information thematic track, held as part of the 17th International Conference on Human-Computer Interaction, HCII 2015, held in Los Angeles, CA, USA, in August 2015, jointly with 15 other thematically similar conferences. The total of 1462 papers and 246 posters presented at the HCII 2015 conferences were carefully reviewed and selected from 4843 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. This volume contains papers addressing the following major topics: context modelling and situational awareness; decision-support systems; information and interaction for driving; information and interaction for learning and education; information and interaction for culture and art; supporting work and collaboration; information and interaction for safety, security and reliability; information and interaction for novel advanced environments.
Context modelling and situational awareness -- Decision-support systems -- Information and interaction for driving -- Information and interaction for learning and education -- Information and interaction for culture and art -- Supporting work and collaboration -- Information and interaction for safety, security and reliability -- Information and interaction for novel advanced environments.
Keywords: Computer science; Information storage and retrieva; Education; User Interfaces and Human Computer Interaction; Computer Applications; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Computers and Education